The development of knowledge management capability in Malaysia's automobile industry: The case of Proton - Sharif, Mohmad Yazam (2004)
The aim of this paper is to present a broad historical analysis of the development of the knowledge management capacity of Malaysia's automobile industry torch bearer, Proton. The company was a joint venture company between the Malaysian government (through its investment arm, Hicom)'and Mitsubishi of Japan. Over time, the government had relinquished its majority shares to DRB, a company owned by the now deceased Yahaya, a private entrepreneur. But subsequently after Yahaya's demise, DRB sold its shares back to the government through the latter's oil company, Petronas. The significance of these changes was that Proton is important to the government.It is important not so much as a car manufacturer but it is a mechanism for the Malaysian government to manage knowledge about the car manufacturing business (human resource management, engineering, R&D, marketing, production, purchasing, international business, supplier's management and finance) and the automotive industry at large.